1997
DOI: 10.1063/1.869459
|View full text |Cite
|
Sign up to set email alerts
|

A thermo-chemical exploration of a two-dimensional reacting supersonic mixing layer

Abstract: The hypervelocity two-dimensional reacting supersonic mixing layer experiments of Erdos et al. with a H 2 /air stream have been simulated with model free fine grid calculations on a N-S solver with full and single step chemistry. Response of the flow to fluctuations in the inflow stream is utilized to examine chemistry fluid flow interactions. A favourable comparison of the computation with experimentally measured wall static pressure and heat transfer data along with flow picture forms the basis for further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…A limited number of efforts have been made on reacting supersonic flows. See, for example, Buckmaster et al [10], Grosch and Jackson [11], Jackson and Hussaini [12], Im et al [13,14], and Chakraborty et al [15]. For a two-dimensional, laminar, nonreacting, boundary layer over a solid body with a pressure gradient, similarity solutions were obtained by Li and Nagamatsu [16], Cohen [17], and Cohen and Reshotko [18] who solved the momentum and energy equations transformed by the IllingworthStewartson transformation (Illingworth [19], Stewartson [20], Schlichting [21]).…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of efforts have been made on reacting supersonic flows. See, for example, Buckmaster et al [10], Grosch and Jackson [11], Jackson and Hussaini [12], Im et al [13,14], and Chakraborty et al [15]. For a two-dimensional, laminar, nonreacting, boundary layer over a solid body with a pressure gradient, similarity solutions were obtained by Li and Nagamatsu [16], Cohen [17], and Cohen and Reshotko [18] who solved the momentum and energy equations transformed by the IllingworthStewartson transformation (Illingworth [19], Stewartson [20], Schlichting [21]).…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborty, 24 et al has carried out direct numerical simulation (DNS) of H 2 -air mixing layer of Erdos experimental case 6 and investigated the effect of fast chemistry, singlestep chemistry and 7 species-7 reaction finite rate chemistry in the thermo-chemical behaviour of reacting mixing layer. The computed DNS database was used to evaluate the existing combustion models 25 . It was shown that finite rate EDC-based combustion model could predict the overall trend of reaction rate profiles although the model predicts a thin reaction zone compared to DNS data.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Higher specific power means a smaller engine, with its various benefits, for the same power level. (14). For a two-dimensional, laminar, nonreacting boundary layer over a solid body with a pressure gradient, similarity solutions were obtained by Li and Nagamatsu (15), Cohen (16), and Cohen and Reshotko (17) who solved the momentum and energy equations transformed by the Illingworth-Stewartson transformation (18,19,20).…”
Section: Background Literaturementioning
confidence: 99%